Panggung Sejarah Terbentuknya Kabupaten Pasangkayu: Sebuah Studi Pustaka (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This research aims to examine in-depth the historical stages of the formation of Pasangkayu Regency through a literature review approach. The primary focus of the research is to explore the historical, social, political, and administrative dynamics underlying the region's formation as an autonomous region. The method used is library research, which involves collecting and analyzing various written sources such as history books, government documents, scientific journals, and archives related to the regional expansion process. The study's findings indicate that the formation of Pasangkayu Regency was inseparable from the aspirations of local communities seeking improved public services, accelerated development, and strengthened regional identity. Furthermore, geographic factors, natural resource potential, and strategic government considerations played a crucial role in the process of regional expansion from its parent region. This process involved a lengthy process, from the discourse of expansion, administrative struggles, to official determination by the central government. The formation of Pasangkayu Regency resulted from a complex interaction between historical, social, and political factors that developed at the time. This research is expected to contribute to enriching local historical studies and serve as a reference for further research on the dynamics of regional expansion in Indonesia.